Analysis of Village Financial Management Based on PERMENDAGRI Number 20 of 2018 in Oebelo Village, Kupang Regency - Timuneno, Antonius Yohanes William (AKSIOMA : Jurnal Manajemen, 2024)
The research focuses on the field of regional finance concentration and aims to analyze the application of PERMENDAGRI Number 20 of 2018 in the financial management of Oebelo Village, Kupang Tengah Subdistrict, Kupang Regency. This research uses a qualitative method with a descriptive approach, with data collection methods of interviews and documentation for 1 month (December 2024 - January 2025). The results of this study indicate that village financial management starting from planning, implementation, administration, reporting and accountability has been running in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018.
Keywords: Village Financial Management; PERMENDAGRI Number 20 of 2018; Oebelo Village